Measurement of Urine, Moisture and Grip Pressure Control of a New Type Panty Toilet for Care - HOSOYA, Syunsuke; ANDO, Yoshinori; NAGAYA, Kosuke; EDA, Keiichi; KOJIMA, Takako (Transactions of the Japan Society of Mechanical Engineers Series C, 2006)
It is heavy jobs to change diapers for bedridden patients. Changing diaper hurts prides of the patient, so that a panty-type toilet, that can be worn to the patient, is of importance, in which feces and urine are washed automatically. In this study, a new-type automatic washing panty type toilet system is presented. The system consists of a rubber made panty type toilet with tubes at both thighs and a torso, and a control system. In the toilet, air expands the tubes, and water leakage is prevented when washing water flows in the toilet. In the toilet, moisture is dried by dry air and controlled to be an appropriate value. There are three important problems in the system, one of which is the prevention of water leak from the panty-type toiled, second is the method of detecting urine and moisture, and the other is the method of control of the tube's grip pressure to the thighs and the torso, because the pressure gives pains to the patient when its value is larger than the appropriate pressure region. The toilet and the control system are constructed, and experimental tests have been performed. It is ascertained that the proposed system is applicable, in principle, in practical use.